Direct measurement of precipitate induced strain in an Al-Zn–Mg-Cu alloy with aberration corrected transmission electron microscopy. (November 2016) - Ying, X.R.; Du, Y.X.; Song, M.; Lu, N.; Ye, H.Q.
Highlights: Strains induced by nanometer-scale precipitates are measured directly in Al alloys. An effective and feasible equivalent dislocation model is proposed for strain simulation. The equivalent dislocation model is based on a series of dislocation pairs at the precipitate/matrix interface. Strain fields induced by strengthening precipitates can be simulated at interfaces along different planes. Abstract: Precipitates and their associated strain fields significantly influence mechanical properties and, consequently, the industrial performance of aluminum alloys. In this work, we present a direct measurement of strains induced by η′ and η precipitates in an Al-Zn-Mg-Cu alloy using aberration-corrected high-resolution transmission electron microscopy and quantitative strain analysis. The results demonstrate that the strain induced by precipitates in the Al-Zn-Mg-Cu alloy shows significant tensile strains perpendicular to the longitudinal direction of the precipitate discs on the side of the discs and along the longitudinal direction at both ends of the η′ and η precipitates. This strain field can be described by an equivalent dislocation model, in which the lattice mismatch between the precipitate and the matrix is equivalent to a series of dislocation pairs along the precipitate/matrix interfaces.